Riverine fish diversity varies according to geographical isolation and land use modification. Issue 19 (30th August 2017) - Nicol, Elizabeth; Stevens, Jamie R.; Jobling, Susan
Abstract: Understanding the environmental factors driving species‐genetic diversity correlations (SGDCs) is critical for designing appropriate conservation and management strategies to protect biodiversity. Yet, few studies have explored the impact of changing land use patterns on SGDCs specifically in aquatic communities. This study examined patterns of genetic diversity in roach ( Rutilus rutilus L.) together with fish species composition across 19 locations in a large river catchment, spanning a gradient in land use. Our findings show significant correlations between some, but not all, species and genetic diversity end points. For example, genetic and species differentiation showed a weak but significant linear relationship across the Thames catchment, but additional diversity measures such as allelic richness and fish population abundance did not. Further examination of patterns in species and genetic diversity indicated that land use intensification has a modest effect on fish diversity compared to the combined influence of geographical isolation and land use intensification. These results indicate that environmental changes in riparian habitats have the potential to amplify shifts in the composition of stream fish communities in poorly connected river stretches. Conservation and management strategies for fish populations should, therefore, focus on enhancing connectivity between river stretches and limit conversion of nearby land to arable or urban use to maintain current levels of biodiversity. Abstract : Our paper contributes to the ongoing debate concerning whether environmental drivers dictate parallel distributions of communities and populations. Results here show that strong parallels of low species diversity and genetic diversity can arise in isolated river stretches running through areas that are increasingly subjected to intensive land use practices (especially arable cropland). Conversion of natural land and physical isolation of fish populations are therefore a major threat to the sustainability of fish species.